Penerapan Permainan Kooperatif terhadap Perkembangan Sosial Emosional Anak Usia Dini - hanna choirunnisa aziz; Rizawati (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2022)
Cooperative games are games related to social communication in a team and encourage the emergence of a togetherness and cooperation of children. Socio-emotional development is a child's development that needs to be stimulated, because it will affect the child's future life, especially when interacting with the environment around the child. This study aims to determine the effect of cooperative games on social emotional development, using research methods (classroom action research) with a population of "children in group A" totaling 9 children, using data collection in the form of observation sheets and cooperative game activities carried out in 2 cycles, so that Researchers can conclude that this cooperative game greatly affects emotional social development because each activity involves social interaction, cooperation between group friends so that children are accustomed to socializing. in the pre-cycle, the child's development is still low 25%. In cycle 1, the effect of cooperative play begins to affect 50%. In cycle 2, the effect of cooperative play is shown, by showing the largest average value obtained from a number of children from one class achieving the criteria for Developing According to Expectations (BSH) with a percentage of 75 %.